2015
DOI: 10.1038/ajg.2015.343
|View full text |Cite
|
Sign up to set email alerts
|

Morbid Obesity Is Associated With Adverse Clinical Outcomes in Acute Pancreatitis: A Propensity-Matched Study

Abstract: Morbid obesity negatively influences inpatient hospitalization and is associated with adverse clinical outcomes, including mortality, organ failure, and health-care resource utilization. These observations and the increasing global prevalence of obesity justify ongoing efforts to understand the role of obesity-induced inflammation in the pathogenesis and management of AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 44 publications
2
64
2
1
Order By: Relevance
“…Other studies have also shown decreasing mortality rates over the last decade, which are further corroborated by our finding of a decrease from 3,749 (1.62%) to 2,130 (0.79%) during the study period. 12,13,1820 . These outcomes are justifiable since milder cases of AP are becoming easier to detect with better testing and complications can be identified earlier in the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown decreasing mortality rates over the last decade, which are further corroborated by our finding of a decrease from 3,749 (1.62%) to 2,130 (0.79%) during the study period. 12,13,1820 . These outcomes are justifiable since milder cases of AP are becoming easier to detect with better testing and complications can be identified earlier in the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…A subject in which close similarities between human and animal models may exist is related to the worsening effects of obesity, especially intrapancreatic fat necrosis, on disease severity 57 . Both diet-induced obesity and congenital forms of obesity are used to model the human state.…”
Section: Animal Models Of Clinical Acute Pancreatitismentioning
confidence: 99%
“…To investigate the controversial association between obesity and mortality in patients with AP, Krishna et al . used data from the NIS (2007–2011) to perform propensity score-matched analyses to compare outcomes for adult inpatients with AP with and without morbid obesity 22 . Morbid obesity was associated with higher frequencies of acute kidney injury (10.8% versus 8.2%; p <0.001) and respiratory failure (7.9% versus 6.4%; p <0.001) and higher odds of mortality (OR 1.6, 95% CI 1.2–2.1) 22 .…”
Section: Recent Advances In Epidemiology and Evaluation Of Acute Pancmentioning
confidence: 99%
“…used data from the NIS (2007–2011) to perform propensity score-matched analyses to compare outcomes for adult inpatients with AP with and without morbid obesity 22 . Morbid obesity was associated with higher frequencies of acute kidney injury (10.8% versus 8.2%; p <0.001) and respiratory failure (7.9% versus 6.4%; p <0.001) and higher odds of mortality (OR 1.6, 95% CI 1.2–2.1) 22 . Finally, following hospital discharge for a first episode of AP, a recent study reported 1-year mortality associated with three independent predictors: readmission within 30 days, higher Charlson comorbidity index, and longer hospitalizations 23 .…”
Section: Recent Advances In Epidemiology and Evaluation Of Acute Pancmentioning
confidence: 99%
See 1 more Smart Citation